2016
DOI: 10.1093/hsw/hlw014
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Smoking Behaviors among Newly Released Justice-Involved Men and Women in New York City

Abstract: Long-term effects of cigarette smoking result in an estimated 443,000 deaths each year, including approximately 49,400 deaths due to exposure to secondhand smoke. Tobacco is a major risk factor for a variety of chronic health problems, including certain cancers and heart disease. In this article, authors present qualitative findings derived from individual interviews with men and women who were incarcerated in New York state and New York City. Participants were 60 racially and ethnically diverse men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Cropsey and Kristeller (2005) also found that 76 per cent of offenders continued to smoke in US prisons after the ban. Similarly, evidence suggests that smoking bans alone have little effect of maintenance of smoking cessation upon release (de Andrade and Kinner, 2017; Valera et al , 2016). On the other hand, evidence has also demonstrated the health benefits associated with these bans.…”
Section: Introductionmentioning
confidence: 99%
“…Cropsey and Kristeller (2005) also found that 76 per cent of offenders continued to smoke in US prisons after the ban. Similarly, evidence suggests that smoking bans alone have little effect of maintenance of smoking cessation upon release (de Andrade and Kinner, 2017; Valera et al , 2016). On the other hand, evidence has also demonstrated the health benefits associated with these bans.…”
Section: Introductionmentioning
confidence: 99%
“…Potential predictors of post-release smoking outlined in this study correspond with findings from research completed in the U.S. and Australia where participants have been followed up after their release. Identified reasons for relapse include a demonstration of resistance to enforced abstinence while in prison; 43 belief that tobacco would alleviate the stress associated with release; 43 , 44 finding smoking pleasurable; 45 resumption of substance misuse; 46 smoking being associated with feelings of/or celebrating freedom; 43 , 47 and returning to homes, housing facilities, or social environments where smoking is prevalent. 43 , 44 Additional reasons for smoking relapse which appear to be specific to the prison system in England and outlined in this study include the use of e-cigarettes as a nicotine maintenance tool, e-cigarette users not taking their prison issue device home, and tobacco confiscated on arrest being returned to prisoners at the point of release.…”
Section: Discussionmentioning
confidence: 99%
“…Identified reasons for relapse include a demonstration of resistance to enforced abstinence while in prison; 43 belief that tobacco would alleviate the stress associated with release; 43 , 44 finding smoking pleasurable; 45 resumption of substance misuse; 46 smoking being associated with feelings of/or celebrating freedom; 43 , 47 and returning to homes, housing facilities, or social environments where smoking is prevalent. 43 , 44 Additional reasons for smoking relapse which appear to be specific to the prison system in England and outlined in this study include the use of e-cigarettes as a nicotine maintenance tool, e-cigarette users not taking their prison issue device home, and tobacco confiscated on arrest being returned to prisoners at the point of release. No research has specifically explored the resumption of tobacco smoking on arrival to open conditions in England, however participants in this study anticipated similar reasons resulting in relapse on release to the community; easy access to tobacco (offered via “smoker packs”) on arrival, using tobacco as a stress relief due to changing circumstances, and entering an environment with high smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed very low availability of nicotine replacement therapy or other tobacco cessation medications for this community corrections population (pharmacotherapy was reported by < 4% of the sample). Valera, Bachman, and Rucker (2016) reported that more than 60% of their sample of formerly incarcerated men on probation or parole desired access to pharmacotherapy. Given the well-established effectiveness of pharmacotherapy at helping individuals successfully quit tobacco (generally increasing the chances that an individual will maintain abstinence over 6 months by 2 or 3 times), along with the desire of JI individuals to utilize pharmacotherapy, individuals within community corrections would benefit from a dramatic increase in access to FDA-approved pharmacotherapy such as nicotine replacement therapies or other prescription medications.…”
Section: Discussionmentioning
confidence: 99%